Generation of Space Shooter Level Using Genetic Approach - Ahmad Hamdani; Wahyu Andhyka Kusuma (Jurnal Informatika, 2019)
In this article, we used genetic algorithm and geometric-based approach to generating level for 2D space shooter game. We used the defined fitness value from game designer to limit the fitness value of the genetic algorithm process. And the geometric-based is used to generate base level from the best chromosome in genetic algorithm. The geometric generator will take a random object for each corresponding game element from the chromosome. This approach minize the time to generating the object, we directly used object geometry for the data in chromosome so it can minimize process and memory cost. This approached minimizing the content that must be created manually. From the result, to generation level with controlled difficulty, we must change the chromosome length too, so the fitness value can fit the target fitness and not show any linear difficulty. Our result showed this method capable of generating different level and controlled difficulty.